West Seti Hydroelectric Project: Assessment of its Contribution to Nepal’s Economic Development - Shrestha, Ratna Sansar (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
The proposed West Seti Hydroelectric Project, 750 MW, is one of the best projects of its genre, because it will not only generate peak-in energy and good quality power but because it will do so at low cost and, furthermore, its implementation will result in fl ood control and dry season augmented fl ow for lower riparian areas. Moreover, export of hydropower to India from this project will result in a carbon offset benefi t which is tradable on the carbon market and has potential as a good source of revenue. This paper evaluates such benefi ts and also ascertains to whom such benefi ts accrue, besides identifying costs (so far unaccounted for). This project's contribution to Nepal's economic development may even be higher by a magnitude if it is to be structured as suggested in this paper. Key words: West Seti; Carbon offset; Downstream benefit; Economic development; Export; Hydropower; Peak-in power; Nepal DOI: 10.3126/hn.v5i0.2478 Hydro Nepal Vol. 5, July 2009 Page:8-17